Lycra® arm splints improve movement fluency in children with cerebral palsy - Elliott, Catherine; Reid, S.; Hamer, P.; Alderson, J.; Elliott, B. (Elsevier BV, 2011)
Aims: To determine changes in upper limb movement substructures that denote fluency of movement in children with cerebral palsy (CP) following lycra® splint wear. Secondarily, to explore the efficacy of lycra® splints for those with spastic and dystonic hypertonia. Design: Randomised clinical trial whereby participants were randomised to parallel groups with waiting list control. Method: Sixteen children (mean age 11.5 years SD = 2.2) with hypertonic upper limb involvement (13 hemiplegia, 4 quadriplegia) were recruited. Children were randomly allocated either to a control group or to wear the lycra® splint for a period of three months. Three-dimensional (3D) upper limb kinematics was used to assess four functional tasks at baseline, on initial lycra® splint application, three months after lycra® splint wear, and immediately after splint removal. Movement substructures of the motion of the wrist joint center were analysed. Results: A significant difference was observed between baseline and three months of lycra® splint wear in the movement substructures; movement time, percentage of time and distance in primary movement, jerk index, normalised jerk and percentage of jerk in primary and secondary movements. The magnitude of changes in normalised jerk and the percentage of jerk in the primary movement from baseline to three months was greatest in children with dystonic hypertonia. Conclusions: The results indicate that lycra® arm splinting induced significant changes in movement substructures and motor performance in children with CP. This research demonstrates that fluency of movement can be quantified and is amenable to change with intervention.